PROJECTED TRENDS IN FRESH OR CHILLED RABBIT AND HARE MEAT PRODUCTION IN ROMANIA AND THE EUROPEAN UNION THROUGH 2035 - Silviu-Ionuț BEIA; Dana TĂPĂLOAGĂ; Cosmin ȘONEA; Lucian-Ionel ILIE; Paul-Rodian TĂPĂLOAGĂ; Cosmina Andreea SMEDESCU; Violeta Elena BEIA; Dragoș SMEDES (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romania and the European Union (EU) have encountered significant declines in recent decades, driven by changing consumer tastes, economic limitations, and changed attitudes towards rabbit meat. This study aims to forecast production trends in Romania and the EU until 2035 by utilizing historical data from FAOSTAT, employing exponential smoothing methods, and assessing model accuracy through statistical error metrics such as Mean Absolute Scaled Error (MASE), Symmetric Mean Absolute Percentage Error (SMAPE), Mean Absolute Error (MAE), and Root Mean Square Error (RMSE). The findings reveal an ongoing decline in production, with Romania anticipated to sustain near-zero levels, while the EU is forecasted to encounter additional output losses. The study indicates that economic challenges, evolving dietary preferences, and heightened competition from other protein sources are factors contributing to the sector's collapse. Opportunities for revival are there through the development of value-added goods, enhanced marketing strategies, sustainable agricultural techniques, and advancements in genetics and nutrition. The findings highlight the need for regulatory interventions and industry adjustments to conform to changing market demands and guarantee the long-term sustainability of rabbit and hare meat production in Romania and the EU.